Epigenetic regulation of immunosuppressive tumor-associated macrophages through dysregulated microRNAs - Aamir Ahmad (233201) (2022)
Macrophages are immune cells that play different roles under different physiological conditions. They are present in all tissues where they primarily protect from bacteria and pathogens in addition to assisting in tissue repair. During tumor progression, macrophages can exert contrasting effects based on the M1 vs. M2 polarization. The M2 macrophages support tumor growth through mechanisms that help suppress immune responses and/or circumvent immune-surveillance. A number of such mechanisms such as production of IL-10 and arginase, and expression of PD-L1, V-domain Ig suppressor of T cell activation and B7 family molecule B7-H4 are now believed central to the immunosuppressive effects of tumor-associated macrophages (TAMs). Emerging data has identified epigenetic regulation of these immunosuppressive mechanisms by small non-coding RNAs, the microRNAs (miRNAs). This review discusses the available literature on the subject, including the exosomes mediated transfer of miRNAs between cancer cells and the macrophages within the tumor microenvironment. A number of miRNAs are now believed to be involved in TAMs’ production of IL-10 and expression of PD-L1 while the information on such regulation of other immunosuppressive mechanisms is slowly emerging. A better understanding of epigenetic regulation of macrophages-mediated immunosuppressive effect can help identify novel targets for therapy and aid the design of future studies aimed at sensitizing tumors to immune responses. Other Information Published in: Seminars in Cell & Developmental Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.semcdb.2021.09.001